Molecular detection, genetic diversity and prevalence of major porcine viral pathogens - Wang, Yin (Kansas State University, 2020)
Infectious diseases of food animals have major impacts on economic returns and public health. Effective surveillance and control of animal diseases are very important, in which rapid and accurate detection of etiological agents play a critical role. Molecular diagnostics have been developed and used extensively. Because of its high sensitivity, high specificity, high-throughput and short turnaround time, molecular diagnostics is considered a powerful tool for detection and identification of infectious agents. Several molecular assays have been developed and validated for major swine virus detections in this dissertation. In Chapter 2.1, a multiplex quantitative real-time PCR assay (mqPCR) was developed to detect and differentiate two porcine circoviruses (PCV) associated with the diseases of similar clinical signs: the novel PCV type 3 (PCV3) and the well-known economically important PCV type 2 (PCV2). In Chapter 2.2, a mqPCR assay was developed and validated for detection and differentiation of three PCV2 genotypes, PCV2a, PCV2b and PCV2d, the most frequently circulating genotypes in the US. In Chapter 2.3, a real‐time RT‐PCR (RT‐qPCR) assay of Seneca Valley virus 1 (SVV‐1) was developed and multiplexed with the published foot-and-mouth virus (FMDV) assays to differentiate the two viruses, which cause clinically similar vesicular diseases in swine. In Chapter 2.4, a real-time PCR assay was developed for rapid detection of African swine fever virus (ASFV). Its current spread in Asia and Europe resulted in significant economic losses on the global swine industry. In Chapter 2.5, the Luminex xTAG assay was developed to detect type 2 porcine reproductive and respiratory syndrome virus (PRRSV-2), one of most economically significant viruses in the US. The multiplexing assay allowed to differentiation of the field strains from the vaccine strains. In the design of the molecular assays described above, the most recent sequence databases were built to obtain high strain coverages. The analytical and diagnostic analyses showed high sensitivities and specificities. Subsequent evaluation of clinical samples of different sample types indicated good diagnostic applicability. Finally, addition of the internal controls helped to monitor extractions and amplification efficiencies and to avoid false negative results. Genetic diversity and prevalence of PCV3 and PCV2 were investigated (Chapter 3.1). It showed high prevalence of PCV3 and PCV2 in the swine herds of the Midwestern region of the US in 2016-2018. The phylogenetic analysis indicated low genetic diversity of PCV3, but high genetic diversity of PCV2. A new genotype, PCV2i, was proposed and the genotypes, PCV2a, PCV2b and PCV2d, were indicated as those circulating in the region. Finally, genetic diversity analysis of Rotavirus C (RVC) was conducted (Chapter 3.2). Thirty-one complete genomes were sequenced with next generation sequencing technology and analyzed with all available published reference sequences. Based on the phylogenetic analysis, several new genotypes were defined here, G18-G31 for VP7, P[22]-P[26] for VP4, R5 for VP1, A9-A12 for NSP1, N9-N10 for NSP2, T7-T9 for NSP3 and E6-E8 for NSP4. Genotyping of the 31 complete genomes indicated reassortment existed in 7 segments, VP7, VP4, VP6, VP2, NSP1, NSP2 and NSP3. The study updated the genotypes of RVC strains to help understand its diversity and evolution.
Keywords: Molecular diagnostics; genetic diversity; prevalence; swine diseases; viruses